Challenges in Law Enforcement of Land and Forest Fires in West Kalimantan - Temmy Hastian; Aman Serah, Yenny; M.Fahmi Hazdan (Universitas Muhammadiyah Palu, 2024)
This article explores the challenges faced by law enforcement against forest and land fires. Forest and land fires in West Kalimantan are environmental problems that often occur every year, especially during the dry season, and have an impact on various aspects of life in the community. Although the laws and regulations have regulated the imposition of sanctions on forest and land-burning perpetrators, as stipulated in Law Number 32 of 2009 concerning Environmental Protection and Management in Article 69 paragraph (1) letter h, in reality, there are still various interpretations. in its application. The problems revealed in this study are what factors influence the optimization of environmental law enforcement against the act of clearing land by burning. Through the normative juridical research method, it was revealed that the results of the study were still finding various interpretations of the prohibition on setting land clearing by burning, which is a factor that affects the non-optimal enforcement of environmental law due to land clearing by burning, especially perceptions of exceptions to the prohibition on setting up land clearing by burning, paying close attention to really local wisdom in their respective areas